Optical properties to be considered in color selection in cosmetic Dentistry: a literature review (Research, Society and Development, 2021)
The aim of this study was to perform a literature review about optical properties and their influence on color selection in cosmetic dentistry. A review of studies available in the literature was performed through bibliographic search in the electronic databases Pubmed / Medline, Lilacs, Science direct and Scielo (scientific electronic library). the following descriptors were used for the research: “optical properties”, “aesthetic dentistry”, “color selection” and “fluorescence”. The articles were selected according to the inclusion and exclusion criteria of the study. Some books with relevant content for this research were also added. As well, it was essential to the availability of the full text for inclusion in the study. The correct choice of color is the process that represents one of the greatest difficulties for professionals, as it depends not only on technique and professional experience, but also on a series of factors related to the environment in which the teeth are inserted. Optical properties are highly relevant in the selection of colors in cosmetic procedures in dentistry. It is important that the professional knows these properties and applies this knowledge in daily clinical practice to obtain the best possible results in their cases.